Classification of the Chorda Tympani: An Endoscopic Study. Issue 3 (30th March 2021) - Uranaka, Tsukasa; Matsumoto, Yu; Hoshi, Yujiro; Iwasaki, Shinichi; Kakigi, Akinobu; Yamasoba, Tatsuya
Abstract : Objectives: To determine the ability of preoperative computed tomography (CT) to predict the variable surgical anatomy of the chorda tympani nerve (CTN) based on endoscopic tympanotomy. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: We identified 192 ears of 162 patients who underwent transcanal endoscopic ear surgery from August 2013 to June 2018. Patients with middle ear malformations, revision surgeries, myringoplasty, and cholesteatoma involving the CTN were excluded. Intervention(s): An intraoperative endoscopic image depicting the chorda tympani was selected for each patient and classified into one of five types. Preoperative CT images were analyzed to match the pictorial classification. Main Outcome Measure(s): The visible tympanic segment of the chorda tympani was classified into the following five types: external auditory canal (EAC), detached, attached long, attached short, and ultrashort. Results: A total of 128 ears from 101 patients ranging in age from 2 to 81 years were enrolled. The EAC, detached, attached long, attached short, and ultrashort types of CTN were found in 7 (5.5%), 6 (4.7%), 84 (65.6%), 18 (14.0%), and 13 (10.2%) patients, respectively. The presence of the EAC type could be predicted by preoperative CT while the other four types could be predicted by binning into two groups, with a sensitivity of 0.61 and specificity of 0.72. Conclusion: The variable anatomy of the chorda tympani nerve can be classified into five major groups based on endoscopic tympanotomy.